2000
DOI: 10.1152/ajpregu.2000.279.4.r1215
|View full text |Cite
|
Sign up to set email alerts
|

Substance P in the nucleus of the solitary tract augments bronchopulmonary C fiber reflex output

Abstract: Bronchopulmonary C fibers defend the lungs against injury from inhaled agents by a central nervous system reflex consisting of apnea, cough, bronchoconstriction, hypotension, and bradycardia. Glutamate is the putative neurotransmitter at the first central synapses in the nucleus of the solitary tract (NTS), but substance P, also released in the NTS, may modulate the transmission. To test the hypothesis that substance P in the NTS augments bronchopulmonary C fiber input and hence reflex output, we stimulated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
58
0
1

Year Published

2002
2002
2005
2005

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(63 citation statements)
references
References 52 publications
4
58
0
1
Order By: Relevance
“…The specific neurokinin receptors mediating these responses are unknown. Previous studies have shown that all three neurokinin receptors are present and functional in regions of the nTS likely containing vagal afferent nerve terminals (32,33,35). We observed that systemic pretreatment with a combination of NK 1 and NK 3 receptor antagonists was equally effective at reducing the laryngeal capsaicin-induced reflex and blockade of all neurokinin receptor subtypes.…”
Section: Discussionmentioning
confidence: 47%
“…The specific neurokinin receptors mediating these responses are unknown. Previous studies have shown that all three neurokinin receptors are present and functional in regions of the nTS likely containing vagal afferent nerve terminals (32,33,35). We observed that systemic pretreatment with a combination of NK 1 and NK 3 receptor antagonists was equally effective at reducing the laryngeal capsaicin-induced reflex and blockade of all neurokinin receptor subtypes.…”
Section: Discussionmentioning
confidence: 47%
“…Thus we speculate that group B neurons may be inhibitory interneurons and could participate in the baroreflex depression reported after microinjection of higher doses of ANG II into this nTS region. In contrast, SP influences respiratory and gastric as well as cardiovascular function (10,24,66,72). Furthermore, the localization of our group B neurons responsive to ANG II and SP in the dorsal medial nTS region (77) is congruent with the distribution of vagal afferent projections from the esophagus and stomach (62,80).…”
Section: Perspectivesmentioning
confidence: 66%
“…The end-expiratory PCO 2 concentration was maintained at 3.0 -4.0% by adjusting the ventilation volume. Before and after the rat was paralyzed with gallamin triethiodide, we evaluated the adequacy of the depth of anesthesia by checking whether rapid variations of arterial BP (ĎŽ5 mmHg) and heart rate (HR; ĎŽ10%) would be caused by paw pinch every 0.5 h throughout the experimental procedure (18). If any one of these responses was found, urethane (0.1-0.2 g/kg) was supplemantally given with an IP injection.…”
Section: Methodsmentioning
confidence: 99%